Integration of the STEAM Approach and the Problem Based Learning Model in Mathematics Learning at the Era of Industrial Revolution 5.0 - Wa Ode Indrawati; Hasnawati (Yayasan Zia Salsabila, 2024)
The Industrial Revolution 5.0 era demands more complex skills, such as critical thinking, creativity, collaboration, innovation and digital literacy. Learning approaches and models in mathematics learning need to be adapted to be more relevant to the needs of the times. The integration of the STEAM approach and the Problem Based Learning model is very suitable for learning mathematics in the current era of the Industrial Revolution 5.0. This research aims to analyze the integration of the STEAM approach and the Problem Based Learning model in mathematics learning in the Industrial Revolution 5.0 era. This research is qualitative research using the literature study method. Data sources are quoted from scientific articles, national and international journals, manuals and digital books and other similar things. Then the data is collected, then the data is analyzed and conclusions are drawn. The results of this research conclude that through the integration of STEAM and PBL models in mathematics learning in the Industrial Revolution 5.0 era, students not only develop a deeper understanding of mathematical concepts, but also gain skills that are relevant to the real world, such as problem solving, critical thinking, collaboration , and communication. It prepares students to become lifelong learners capable of facing complex challenges in an ever-changing society.